BUSINESS DEVELOPMENT BASED ON VECTOR WORK WITH BUYERS - O. Ivanova; L. Gvozdeva (Вестник университета)
The possibility of using ABC and XYZ analysis to systematize customers by degree of reliability by group positions has been presented. The approach of vector work with customers has been proposed, which implies the assessment of receivables by means of their ranking by key criteria, identifying those, who are less exposed to the risk of default on money. The basis for the implementation of the formulated information base can be used when building an evaluation card of buyers - debtors for taking specific measures for business development.